Verschluss des Pankreasstumpfes bei Links- und Segmentresektion: Naht, Stapler, Deckung oder Anastomose? - Michalski, Christoph; Tramelli, Paola; Büchler, Markus W.; Hackert, Thilo (Der Chirurg, 2017)
Postoperative pancreatic fistulas represent the most frequent complication after distal and segmental pancreatectomy and occur with a frequency of up to 50 %. There are many technical variations of pancreatic stump treatment for reduction of fistula rates after distal resection. Most of these techniques have only been analyzed in retrospective studies and the evidence for or against a specific technique is low. Several retrospective trials have been conducted with good results to compare suturing with stapled closure of the remnant and to assess the effect of a vascularized falciform ligament patch in reducing postoperative pancreatic fistula; however, in a recently published randomized trial, which analyzed closure of the remnant with a pancreaticojejunostomy compared to standard closure, these results could not be confirmed. Because stapler resection and closure is the most commonly used technique in laparoscopic distal pancreatectomy, there are a large number of studies which assessed various novel methods of improving stapling. Extended stapler compression time and mesh augmentation of the stapler line can be valid methods to reduce fistula rates. Central pancreatectomy is a relatively rarely used procedure where the right-sided pancreatic remnant is closed in the same fashion as during distal pancreatectomy and the left-sided remnant is connected to the intestines with a pancreaticojejunostomy or pancreaticogastrostomy. In conclusion, postoperative pancreatic fistula rates are still a relevant clinical problem after distal pancreatectomy and further studies on potentially improved novel techniques are required.